Construction of Long-Span Bridge Bearing Platforms in Deep and Thick Silt Interlayers - Kang Yang; Wenbin Zhang; Puyu Li; Didi Hao; Chunfeng Wan; Changqing Miao (Advances in Civil Engineering)
The construction of long-span bridge bearing platforms in deep and thick silt interlayers presents challenges such as difficult pit excavation, high risk of foundation pit base uplift, ensuring the secure embedment of the foundation pit cofferdam, and the susceptibility of large-volume concrete to cracking. This paper examines the construction of the main pier bearing platform for the new Yue-Dong Bridge. It compares and selects the optimal cofferdam scheme, ultimately employing a combined cofferdam structure that integrates underwater high-pressure rotary piling for base reinforcement and steel sheet piles. An underwater high-pressure rotary piling fast reinforcement construction process was developed and implemented, alongside the “four-stage dry bottom sealing” strategy to mitigate uplift risks. To address the cracking induced by the heat of hydration in large-volume concrete, a temperature control strategy for large-volume concrete construction was proposed. Real-time monitoring of the cofferdam was conducted to ensure construction safety. Additionally, to verify the effectiveness of the temperature control measures and ensure compliance with temperature control standards, real-time temperature monitoring was also performed during the construction of the large-volume concrete bearing platform. To ensure construction safety, cofferdam displacements and stresses are monitored in real time. The practice has demonstrated that the construction scheme, strategies, and corresponding measures are effective, leading to the successful construction of the long-span bridge bearing platforms for the Yue-Dong Bridge in deep and thick silt interlayers. The key technologies developed and applied in this paper offer significant and valuable insights for the construction of similar bearing platforms.